A comparative study of university training of sports and physical activity kinesiologist - Giovanni Esposito; Rosario Ceruso; Sara Aliberti; Tiziana D'Isanto; Francesca D'Elia (BMC, 2024)
Abstract Background In Italy, Legislative Decree No. 36/2021 and Ministerial Decree (MD) No. 1649/2023 have redefined the professional landscape of the physical activity and health sectors, emphasizing interdisciplinary and wellness-oriented education. The current disparity in the weighting of formative elements among the biomedical, psycho-pedagogical, and Exercise and Sport Sciences (ESS) fields in the configuration of degree courses in ESS has led to a need for reform. MD No. 1649/2023 offers an opportunity to reform these courses to emphasize interdisciplinary and wellness-oriented objectives, including at least 20 ECTS credits of practical activities in ESS disciplines. However, the impact of practical and laboratory activities on future kinesiologists has never been studied. This study aims to evaluate the impact of physical activity habits on the performance and self-assessment of ESS students. Method A sample of 56 students enrolled in the Master of Science in Sport Science and Techniques at the University of Salerno was divided into "active" and "inactive" groups based on their physical activity levels, according to WHO guidelines. Both groups underwent anthropometric and functional tests, including the Squat Jump (SJ) and Countermovement Jump (CMJ). Descriptive statistics and t-tests assessed the differences between and within groups. Results The "active" group exhibited significantly higher performance in SJ (15.7% higher) and CMJ (18.5% higher) compared to the "inactive" group. Both groups showed significant improvements in jump height from SJ to CMJ, with the "active" group improving by 11.04% and the 'non-active' group by 7.38%. Conclusion Continuous physical activity enhances functional efficiency, with significant gains in explosive and reactive strength. Practical, evidence-based training is crucial for future kinesiologists to provide specialized services and promote health, underscoring the importance of integrating substantial practical activities in ESS degree courses.